(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study was designed to find out the competencies possessed by upper basic education level teachers for teaching business studies in Anambra State. The study was guided by three research questions and three null hypotheses. The study adopted survey research design. Questionnaire was the instrument used for data collection. Mean and standard deviation were used to answer the research questions while t- test was used for hypotheses testing. The result indicated that out of the twenty two competencies identified by the study, only eleven were possessed by the business studies teachers. The competencies possessed included among others; selecting the topic to be taught, stating specific objectives to be achieved, effective knowledge of the subject matter as well as relating course of study to measurable performance objectives. However, the competencies not possessed by the teachers include among others; proper hanging of charts and pictures and constructing valid and reliable test to evaluate students’ progress. It was found out that there was no gender bias regarding the competencies possessed by teachers. The recommendations among others were that; all the identified competencies which the business studies teachers needed to improve on be packaged for use during in- service training of teachers in Anambra State and that government should organize seminars and workshops for teachers in the areas of the identified competencies lacking for improvement.